2020
DOI: 10.1002/1878-0261.12783
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are recruited to hepatocellular carcinoma tissues in a CX3CL1‐CX3CR1 dependent manner and induce tumour cell apoptosis

Abstract: The mechanisms and biological functions of migrating platelets in cancer remain largely unknown. Here, we analyzed platelet infiltration in hepatocellular carcinoma. We detected platelet extravasation in both mouse and human HCC tissues. CX3CL1 directly induced platelet migration, and hypoxia enhanced platelet migration by upregulating CX3CL1 expression. Knocking down CX3CL1 in HCC cells reduced platelet migration in vitro, as well as infiltration of HCC tissue in an orthotopic HCC mouse model. Components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…35 In this study, we revealed that fractalkine/CX3CL1 was also up-regulated even by a low-intensity resistance exercise. 37 Further, gene therapy with fractalkine/CX3CL1 has been reported to induce tumor-specific cytotoxic T cells and inhibited tumor growth, leading to an increase in survival of HCC-bearing mice. 38 Moreover, Chen et al reported fractalkine/CX3CL1 stimulated chemotactic migration and cytotoxicity in natural killer cells via signal transducer and activator of transcription 3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this study, we revealed that fractalkine/CX3CL1 was also up-regulated even by a low-intensity resistance exercise. 37 Further, gene therapy with fractalkine/CX3CL1 has been reported to induce tumor-specific cytotoxic T cells and inhibited tumor growth, leading to an increase in survival of HCC-bearing mice. 38 Moreover, Chen et al reported fractalkine/CX3CL1 stimulated chemotactic migration and cytotoxicity in natural killer cells via signal transducer and activator of transcription 3 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are recruited into the HCC tissue by tumor cell-derived CX3CL1 [ 105 ] and get activated. A unique tumor-specific feature is platelet activation by HCC-derived IgGs via FcγRIIa, which is upregulated in hyperreactive platelets of HCC patients [ 106 ].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…A unique tumor-specific feature is platelet activation by HCC-derived IgGs via FcγRIIa, which is upregulated in hyperreactive platelets of HCC patients [ 106 ]. Cytological smears from human HCC biopsies show that activated platelets cluster in close proximity to tumor cells [ 105 , 107 , 108 ] and adhere via GPIIb/IIIa, GPIb-IX-V and P-selectin receptors [ 108 , 109 ]. The inhibition of platelet activation with clopidogrel reduces the binding of platelets to hepatoma cells and prevents tumor growth [ 110 ].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was shown that miR-561-5p downregulated CX3CL1 mRNA expression, leading to a decrease in chemotaxis, functional regulation and infiltration of CX3CR1 + NK cells, thus promoting HCC growth and lung metastasis ( 39 ). Miao et al ( 40 ) demonstrated that members of the CX3CR1/Syk/PI3K signaling pathway were essential for CX3CL1-induced platelet migration, which induced apoptosis of HCC cells in vitro , thus inhibiting HCC growth. These studies suggest that CX3CL1/CX3CR1 are potential therapeutic targets against HCC growth and metastasis.…”
Section: Hcc-associated Chemokinesmentioning
confidence: 99%